2022
DOI: 10.1073/pnas.2111051119
|View full text |Cite
|
Sign up to set email alerts
|

Synaptotagmin-1 is a bidirectional Ca 2+ sensor for neuronal endocytosis

Abstract: Significance Precise and efficient coupling of endocytosis to exocytosis is critical for neurotransmission. The activity-dependent facilitation of endocytosis has been well established for efficient membrane retrieval; however, whether neural activity clamps endocytosis to avoid excessive membrane retrieval remains debatable with the mechanisms largely unknown. The present work provides compelling evidence that synaptotagmin-1 (Syt1) functions as a primary bidirectional Ca 2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
0
10
2
Order By: Relevance
“…snt-1(md290) mutants displayed more severe recycling defects after strong stimulation, indicating that it is dispensable for recycling at lower activity. This is in stark contrast to previous results in mammalian hippocampal neurons in which synaptotagmin-1 promotes slow small-scale endocytosis, while inhibiting bulk retrieval during sustained neurotransmission (Chen et al, 2022). Although a role of SNT-1 in the slow clathrin-mediated endocytosis is likely also in C. elegans and simply not efficiently reported by pOpsicle, a role in inhibition of bulk endocytosis might not be conserved between nematodes and mammals.…”
Section: Discussioncontrasting
confidence: 99%
“…snt-1(md290) mutants displayed more severe recycling defects after strong stimulation, indicating that it is dispensable for recycling at lower activity. This is in stark contrast to previous results in mammalian hippocampal neurons in which synaptotagmin-1 promotes slow small-scale endocytosis, while inhibiting bulk retrieval during sustained neurotransmission (Chen et al, 2022). Although a role of SNT-1 in the slow clathrin-mediated endocytosis is likely also in C. elegans and simply not efficiently reported by pOpsicle, a role in inhibition of bulk endocytosis might not be conserved between nematodes and mammals.…”
Section: Discussioncontrasting
confidence: 99%
“…snt-1(md290) mutants displayed more severe recycling defects after strong stimulation, indicating that it is dispensable for recycling at lower activity. This is in stark contrast to previous results in mammalian hippocampal neurons in which synaptotagmin promotes slow small-scale endocytosis, while inhibiting bulk retrieval during sustained neurotransmission (Chen et al, 2022). Although a role of SNT-1 in the slow clathrin-mediated endocytosis is likely also in C. elegans and simply not efficiently reported by pOpsicle, a role in inhibition of bulk endocytosis might not be conserved between nematodes and mammals.…”
Section: Discussioncontrasting
confidence: 96%
“…The efficiency of endocytosis and exocytosis is crucial to establishing efficient neuronal transmission. SYT1 helps to establish this via a bidirectional Ca 2+ sensing capability that links endocytosis and exocytosis [ 35 ]. Previous labs have recognized that SYT1 is able to initiate slow and small clathrin mediated endocytosis (CME) and/or block bulk-sized endocytosis during increased neural activity [ 35 ].…”
Section: Synaptotagmin Isoforms and Syt1 Functionmentioning
confidence: 99%
“…SYT1 helps to establish this via a bidirectional Ca 2+ sensing capability that links endocytosis and exocytosis [ 35 ]. Previous labs have recognized that SYT1 is able to initiate slow and small clathrin mediated endocytosis (CME) and/or block bulk-sized endocytosis during increased neural activity [ 35 ]. In contrast to the pivotal role of C2B in exocytosis, it has been demonstrated that either C2B or C2A can be involved in SYT1-mediated endocytosis [ 1 ].…”
Section: Synaptotagmin Isoforms and Syt1 Functionmentioning
confidence: 99%
See 1 more Smart Citation